Predictors of Reading and Spelling Words Change as a Function of Syllabic Structure in Spanish - Martínez, Naroa (Colegio Oficial de Psicólogos de Madrid, 2020)
We investigated the longitudinal predictors of reading and spelling of words and pseudowords with different syllabic structures in a shallow orthography. Participants were 47 Spanish-speaking children from kindergarten to second grade. Letter knowledge, phonological awareness, and rapid automatized naming were evaluated at the beginning and at the end of the school year, and reading and spelling skills were assessed at the beginning of the following year. Hierarchical multiple regression analysis revealed that letter knowledge was the strongest predictor of reading and spelling words and pseudowords with simple syllables after 6 and 12 months. Phonological awareness predicted reading and spelling stimuli with complex syllables. Mediation analysis confirmed the mediator role of phonological awareness in the relationship between letter knowledge and reading and spelling with complex syllabic stimuli. This research provides longitudinal evidence that the syllabic structure determines the role of letter knowledge and phonological awareness in reading and spelling skills in Spanish. Understanding the knowledge that is key to learning to read and write may lead to improving methods and materials for literacy in Spanish language.